Elizabethkingia meningoseptica: an emerging threat - Shah, Zalak; Soodhana, Dhanya; Kalathia, Mitul; Parikh, Yogesh (International Journal of Contemporary Pediatrics, 2017)
Infection by Elizabethkingia meningoseptica (E.meningoseptica) is very rare. It is associated with neonatal meningitis and other infections, especially in preterm neonates. We report a case of preterm neonate infected by E.meningoseptica clinically presented with meningitis and necrotizing enterocolitis. The patient succumbed in spite of timely diagnosis and institution of appropriate antibiotics. Although rare but infections casued by E.meningoseptica are often severe and life threatening. It should be considered as an emerging threat and efforts to identify and prompt treatment should be considered in neonates suffering from meningitis.